2020
DOI: 10.1007/s00167-020-06051-z
|View full text |Cite
|
Sign up to set email alerts
|

Is robotic-assisted unicompartmental knee arthroplasty a safe procedure? A case control study

Abstract: PurposeThe hypotheses were that firstly there is few early specific complications due to the use of a robotic‐assisted system for unicompartimental knee arthroplasty (UKA), and secondly there are less revisions and complications after robotic‐assisted UKA than after conventional UKA. Methods200 robotic‐assisted UKA (175 patients) and 191 conventional UKA (179 patients) were performed between 2013 and 2018 from the same center. Revisions, intraoperative and postoperative complications, functional and radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…Only some minor complications related to the use of navigation pins are described [ 105 , 106 ]. Similar results have been described with the Navio system [ 107 ].…”
Section: Robotic-assisted Knee Arthroplastysupporting
confidence: 87%
“…Only some minor complications related to the use of navigation pins are described [ 105 , 106 ]. Similar results have been described with the Navio system [ 107 ].…”
Section: Robotic-assisted Knee Arthroplastysupporting
confidence: 87%
“…Then, several studies have shown a decrease in postoperative pain with the use of the robot [ 20 , 21 ]. This may also explain the decrease in the rate of stiffness in patients operated with robotic.…”
Section: Discussionmentioning
confidence: 99%
“…25 Mergenthaler et al reported no complications related to the use of the robotic system. 26 Pearle et al suggested that no further rigid fixation device is necessary, which reduces potential complications such as infection, iatrogenic fractures or soft tissue injury caused by the weight and movement of the robot. 27 However, there were no significant differences in non-implant-specific complications between the two techniques in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%